The Unified Strength Theory for Plastic Limit Load Analysis of Vertical Shaft Lining - Guangsi Zhao; Minghui Ren; Xianhao Qiu; Qinghua Xue (Advances in Civil Engineering)
Plastic limit analysis is a significant application for structural design and failure prediction, implying that the potential bearing capacity of material can be fully considered. Meanwhile, the failure process of structures usually occurs in the deformation of the plastic stage. Hence, it is important to investigate the mechanical properties of structures in the plastic state through proper mechanical models and principles. In this paper, the analytical stress expression and formulas for computing plastic limit load have been deduced based on the unified strength theory. Additionally, the relationships between plastic limit load of the shaft lining and the strength differential (SD) of structural material, the geometrical characteristic (R0/R) and the intermediate principal shear stress (b) have been discussed. Finally, the method of the plastic limit load is adopted for the safety evaluation of the shaft lining through a practical case.